Study on risk management in preparation stage for expressway construction projects in Vietnam - Duc, Nguyen Minh; Hoang, Nguyen Ba (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2022)
The expressway projects in Vietnam are being in thriving because these projects play an important role in the national economy. However, in the project preparation phase, many risk factors have emerged. These risk factors directly and seriously affect the performance of the entire project. Many expressway projects have been delayed and costly exceeded over the recent years. This article focuses on the current situation of the risks of expressway projects in Vietnam, thereby analyzing and studying the risk factors affecting the project, considering the level of impact of these risk factors on expressway projects. This analysis will clarify the main risk elements for expressway projects when the implementation of these projects involves complex policy issues, socioeconomic status, technical issues, and the conflict between the parties involved in the project.